(x² - 4x - 60)/(x² - 100)
Numerator = x² - 4x -60
= (x - 10)(x + 6)
Denominator = x² - 100
= x² - 10²
= (x - 10)(x + 10)
So (x² - 4x - 60)/(x² - 100)
= (x - 10)(x + 6)/[(x - 10)(x + 10)]
= (x + 6)/(x + 10)
2006-10-18 09:29:48
·
answer #1
·
answered by Wal C 6
·
0⤊
0⤋
(x^2-4x-60)/(x^2-100)
If the numerator and denominator can be factored and they have a factor in common, the common factor can be cancelled out.
x^2 - 100 = (x + 10)(x - 10) [difference of two squares]
Looking at the numerator, you hope that one of its factors is (x - 10) [because the coefficient of the x term is -4]
x^2 - 4x - 60 = (x - 10)(x + 6)
The fraction is now
(x - 10)(x + 6)/(x + 10)(x - 10)
(x + 6)/(x + 10)
2006-10-18 09:30:17
·
answer #2
·
answered by kindricko 7
·
0⤊
0⤋
Denominator is easiest: it's the difference of two squares and thus is factored to the sum and difrference:
x^2-100 = (x-10)*(x+10)
For the numerator, can you find two numbers that
when multiplied = -60
and
when added equal -4 ?
How about -10 and +6 ?
So, the numerator is factored into (x-10)*(x+6) right?
Put it together and cancel the common factor on top and bottom
2006-10-18 09:25:52
·
answer #3
·
answered by modulo_function 7
·
0⤊
0⤋
x^2-4x-60 = (x-10)(x+6)
x^-100 = (x-10)(x+10) give the a^2 - b^2 = (a-b) (a+b)
so we get
(x-10)(x+6)
------------------------
(x-10) (x+10)
Answer: (x+6)/(x+10)
2006-10-18 09:26:01
·
answer #4
·
answered by Wil T 3
·
0⤊
0⤋
x+6
-----
x+10
2006-10-18 09:25:46
·
answer #5
·
answered by RV 2
·
0⤊
0⤋
[(x^2-4x-60)/(x^2-100)]
(x-10)(x+4)/((x-10)(x+10))
(x+4)/(x+10)
2006-10-18 09:25:33
·
answer #6
·
answered by yupchagee 7
·
0⤊
0⤋
(x^2-4x-60)/(x^2-100)=((x-2)^2-64)/(x^^2-10^2)
=((x-2)^2-8^2)/(x^2-10^2)
=(x-2-8)(x-2+8)/(x-10)(x+10)
=(x-10)(x+6)/(x-10)(x+10)
=(x-6)/(x+10)=(x+10-16)/(x+10)=1-16/(x+10)
2006-10-18 11:41:44
·
answer #7
·
answered by Majdi B 3
·
0⤊
0⤋